Jump-landings that supersede bone health threshold requirements for premenopausal women - Tracey Clissold; Cronin JB; De Souza MJ; Winwood PW (Archives of Sports Medicine and Physiotherapy - Peertechz Publications, 2022)
Osteoporosis is a disease characterized by a reduction in the density and quality of bone leading to a weakness of the skeleton and associated increased risk of fracture [1]. The most common type of osteoporosis is termed primary osteoporosis and includes both postmenopausal and age-related osteoporosis,